Improvement of the normative monetary evaluation of settlement land in the ecological context - Popov, Andriy; Trehub, Olena (Geodesy and Cartography, 2022)
The ecological factors affect not only the quality of life and health of settlement residents but also the real property market and land valuation indicators. However, no previous Ukrainian study has considered ecological factors during calculating the normative monetary valuation (NMV) of settlement land. Much uncertainty still exists about the nature of selecting ecological factors, their calculating, interpreting and application. This study aims to identify the ecological factors and their indexes and propose a new approach for defining the ecological impact on the NMV of the settlement land and evaluation units. A retrospective study collected infrastructural, environmental, and ecological data for the Kharkiv city, covering the years 2014–2019. The empirical methods and GIS tools were used to evaluate and interpret the data. The indexes characterising the ecological condition led to an increase in the minimum index for the normative monetary land value within the evaluation districts from 9.71 USD/sq. m. to 12.00 USD/sq. m. and the maximum value – decreased from 101.60 USD/sq. m. to 86.34 USD/sq. m. The new approach takes into account the area of environmental factors distribution within the evaluation unit and proves usefulness in understanding the actual ecological impact on the NMV of settlement land. Overall, this study has demonstrated that the size of land valuation is slightly influenced, although not significantly, by ecological factors.